Implementasi Metode Logarithmic Image Processing (LIP) Untuk Penajaman Warna Citra Hasil Screenshot - Matondang, Nur Hayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Screenshots or screenshots of monitors such as smartphones, tablets and computer devices. The resulting screenshot image has a small level of smoothness and image sharpness. The level of smoothness and sharpness is said to be one of the main factors in image processing, so zooming is usually done to produce a better image directly but has a poor brightness level. The problem that often arises is that screenshot images have colors that are less bright or dark, making it difficult to understand the contents of the image. This situation will affect the sharpening of the colors in the screenshot image you want to take. Images that have less bright colors can cover up the information contained in the image. For the process of sharpening the color of a screenshot image, a method is needed so that the image can be sent properly.